COMBINING MODIFIED ATMOSPHERE PACKAGING AND NISIN TO EXTEND THE SHELF LIFE OF ATLANTIC SALMON (SALMO SALAR) - Han, Dong (Clemson University Libraries, 2014)
Atlantic salmon is often used in laboratory experiments to represent marine fishes. Many researchers try to optimize the levels and dosage of preservatives to maintain the freshness and extend the shelf-life of Atlantic salmon. Little information has been provided about the effectiveness of combined method between MAP and nisin, especially on the preservation of Atlantic salmon. Strong evidences suggest that MAP associated with nisin may have a potential to improve Atlantic salmon storage quality. Preservation effectiveness of combining modified atmosphere package (MAP) and nisin on fresh Atlantic salmon was determined using various methods. Six groups of farmed Atlantic salmon were purchased from local market and treated with using MAP (19 % CO2 / 70 % N2 /11 % O2 , 38 % CO2 / 51 % N2 /11 % O2 and air) and nisin (400 IU/g or not applied). Microbiological enumeration (aerobic plate count, psychrotrophic bacteria and lactic acid bacteria) and TVB-N test were conducted on Day 0, 2, 4, 7 and 10 of refrigerated storage. Package headspace gas composition and sensory evaluation were carried out on Day 0, 2 and 4. The presence of CO2 effectively inhibited the growth of bacteria while nisin only inhibited the growth of aerobic microorganisms. TVB-N test indicated that CO2 can efficiently delay the spoilage of Atlantic salmon while nisin has less of an impact on Atlantic salmon shelf-life. The experiments support the combination of modified atmosphere package and nisin as an effective method to limit the spoilage of Atlantic salmon compared to traditional preservation methods.